SOCIAL DYNAMICS OF CHANGES IN REORGANIZATION OF NON-CLASSICAL GYMNASIUMS INTO NON-CLASSICAL SECONDARY SCHOOLS OF PRACTICAL DIRECTION (1866-1872) - Бондаренко, Галина (SWorldJournal, 2023)
The article deals with the process of reorganization of the non-classical gymnasiums into non-classical secondary schools, on the basis of archival, little known and published sources (1866-1872). Organizational and substantive principles of reorganizatio